Spread of virus and evolution of its genome in populations of domestic ruminants : Application to molecular epidemiology and surveillance of 'Peste des petits ruminants' - (:unkn) unknown (My University, 2015)
Peste des petits ruminants (PPR), caused by a Morbillivirus is one of the most important viral infections in sheep and goats. It is widely spread in Asia, Middle East and Africa. In Africa, it is an emerging disease in the north and the south of the continent. It is a major factor of food insecurity for the farming population (70% of the poor population in the tropical regions). PPR is a study model of transboundary diseases; its spread is highly related to regional movements of livestock. Understanding the spread of PPR is an essential condition for the implementation of efficient control measures (vaccination, quarantine, border controls etc.). Up to our knowledge, no studies have investigated the range of genetic diversity of PPR virus (PPRv) during natural infections in small ruminants and the accumulation of virus mutations during its spread. Further on, in tropical countries with extensive farming, animal identification and traceability are a current problem. In such conditions, the genetic diversity of the PPRv can be used as a marker of animal movement and spread of the virus. The objective of this study was to investigate the genetic diversity of the PPRv in order to characterise the actual viral lineages and to retrace the transmission of the virus in Senegal and its surrounding countries. Analyzing two complete viral genes of the PPR, we have estimated the rate of evolution of this virus, in a four year period, between 2010 and 2014. The results of the study show that the first strains of lineage II of PPRv have been introduced in 2005 in Senegal and its surrounding countries. Molecular clock analysis and phylogeographical reconstitution of the PPRv indicate that the lineage II, actually enzootique in western Africa, has its origins in Nigeria. This viral introduction from the direction east towards west, corresponds to the transboundary movement and commerce of livestock in the countries of western Africa, which represents the economic and
Keywords: African Research